Promoting Student Interdisciplinary Learning: Mechanisms, the Learning Environment Design Model, and Empirical Research - Wan, Kun (Best Evidence in Chinese Education, 2024)
Interdisciplinary learning has become a highly recommended learning approach in Chinese compulsory education. Nevertheless, there exist a variety of problems with the current implementation of interdisciplinary learning, such as misconception of the approach and a lack of purposeful design. This study analyzed the mechanisms for promoting student interdisciplinary learning, constructed a model for interdisciplinary learning environment design, and conducted practical research based on the model.